IMPLEMENTASI FATWA DSN-MUI NO. 108/DSN-MUI/X/2016 TENTANG PEDOMAN PENYELENGGARAAN PARIWISATA BERDASARKAN PRINSIP SYARIAH PADA DESTINASI WISATA TALAO PAUH KOTA PARIAMAN - Fina Marliza Putri; Dewi Manda Angraini (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This research was conducted at the Talao Pauh Tourist Destination, which is one of the tourist destinations in Pariaman City that strives to become a leading tourist destination at the national and international levels as stated in the vision of Pariaman City, namely the City of Tourism, Trade, Religion, and Cultural Services of Pariaman. The purpose of this study is to determine the implementation of the DSN-MUI fatwa number 108 / DSN-MUI / X / 2016 at the Talao Pauh Tourist Destination, Pariaman City. The method used in this study is a qualitative method with a qualitative descriptive approach. Data collection was carried out through observation, interviews, and documentation. Based on this study, it can be concluded that the Talao Pauh Tourist Destination has partially implemented sharia principles, including the existence of places of worship, namely prayer rooms, separate ablution places for men and women, the existence of various tourist attractions that do not lead to pornography and idol worship such as playgrounds, water rides, tourist bridges, and food provided at this tourist destination is also a local culinary dish that is definitely halal. However, there are still aspects that need to be considered, namely the lack of supervision of visiting tourists, such as becoming a place for couples who are not legally married, which is not in accordance with the DSN-MUI Fatwa because tourist destinations must be protected from immoral acts and adultery. Furthermore, maintenance of public toilet facilities and improving cleanliness around tourist areas need to be considered to ensure compliance with the DSN-MUI fatwa that tourist destinations must maintain cleanliness, natural sustainability, sanitation, and the environment.